Cell wall metabolism: The Yin and Yang of fruit postharvest biology - Labavitch, J. M. (2015)
For the fruit postharvest physiologist, discussions of cell wall metabolism initially bring to mind the processes associated with the fruit softening that occurs during ripening. Fruit softening traditionally has been equated to the series of apoplast-localized events that lead to textural changes, which are desired by most consumers. Among these events, the enzyme-catalyzed breakdown and solubilization of cell wall polysaccharides are considered to be crucial in most fruit. The goal of this paper is to help us to see fruit softening in terms of a series of mechanistically connected wall metabolism processes that ends with the familiar texture changes, but which may influence a good deal more of the developmental and metabolism transitions that occur as a fruit ripens. Yin and Yang are terms that describe the apparently opposing, but occasionally complementary, sides of the same entity. The postharvest biologist certainly must apply this perspective to his/her view of the ripening fruit’s cell wall metabolism. In general, the most costly fruit postharvest management problems are associated with poorly controlled ripening (the softening aspects, in particular) and losses to pathogens. Our work with tomato fruit demonstrates a Yin/Yang-like connection between (1) the wall metabolism events that control ripening and (2) the processes that convert an unripe, pathogen-resistant tomato to a fully ripe, pathogen-susceptible fruit. A biologist who studies the evolution of angiosperms would most likely see the ripening fruit’s softening and increasing pathogen susceptibility as behaviors that contribute to seed dispersal and the eventual success of well-adapted species. A longer-term goal of this research is to understand the genetic basis of this linkage and then sever it, thus enabling the delivery of ripe and pathogen-free fruit to consumers.